A research of mathematical model for diagnostical tests - Kosareva, Natalja; Krylovas, Aleksandras (Lietuvos matematikos rinkinys, 2009)
The technology of creation dichotomous diagnostic operators as general testing tool using the empirical data is proposed. The only requirement to diagnostic operator – it must be nondecreasing function. Probability distribution of test result and test information are calculated according to the proposed technique.